(untitled) (Research, Society and Development, 2022)
The educational environment has an important influence on the health of adolescents, becoming an appropriate environment for the development, support and promotion of projects that lead to health, especially oral health, becoming an appropriate space for the construction of healthy habits, when incorporated into a daily-didactic program or project. Thus, the present study is an integrative review that aims to analyze how educational practices in oral health carried out with schoolchildren contribute to changing habits in relation to oral hygiene in adolescents. For this, an integrative review study was carried out between July and December 2021 based on national and international journals addressing issues related to the topic. The databases consulted were: 1. CAPES - Coordination for the Improvement of Higher Education Personnel and 2. LILACS - Latin American and Caribbean Literature on Health Sciences. The research involved the following combinations of keywords: (a) oral health AND educational practices AND school; (b) oral health AND educational practices AND adolescents; (c) oral health promotion AND adolescents. From the definitions, criteria and combinations of keywords defined for the study, 363 publications were located. The final sample consisted of 10 articles. It is concluded, therefore, that the educational practices in oral health carried out with schoolchildren determine a positive result in the promotion of oral health for adolescents, reflecting in the increase of their awareness regarding the importance of oral health care.